Vertical and island-scale structuring of bacterial and archaeal communities in Pinus merkusii forest soils - RULLY ADI NUGROHO; NICO M. VAN STRAALEN; WILFRED F. M. RÖLING (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Nugroho RA, van Straalen NM, Röling WFM. 2026. Vertical and island-scale structuring of bacterial and archaeal communities in Pinus merkusii forest soils. Biodiversitas 27 (3): d270313. https://doi.org/10.13057/biodiv/d270313. Environmental and spatial processes contribute to the structuring of soil microbial communities, but the relative importance of vertical and horizontal gradients is poorly understood in tropical archipelagic forests. The vertical and spatial distributions of bacterial and archaeal communities were examined in Pinus merkusii forest soils across 12 sites on five Indonesian islands (36 composite samples). Litter (L), fragmented litter (F), and mineral (M) soil layers were analyzed using denaturing gradient gel electrophoresis (DGGE) to characterize dominant community profiles. Community dissimilarity was assessed using Mantel and partial Mantel tests, and compositional variance was assessed using PERMANOVA. Bacterial communities were strongly vertically stratified. Mantel tests showed significant correlations between community dissimilarity and soil layer (r = 0.52, p < 0.001) and geographic distance (r = 0.60, p < 0.001), which remained significant in partial correlations. PERMANOVA indicated that soil layer explained 43.5% of the variation (pseudo-R2 = 0.435, p < 0.001), whereas island identity explained 15.1% (pseudo-R2 = 0.151, p = 0.0135). In contrast, archaeal communities showed no significant association with either geographic distance (r = −0.03, p = 0.68) or soil layer (r = −0.04, p = 0.80). In contrast, PERMANOVA revealed strong differentiation among island identity (pseudo-R2 = 0.375, p = 0.0045). These findings reveal contrasting domain-specific spatial organization of microbial communities, with bacteria primarily structured by vertical habitat differentiation and distance–decay patterns, whereas archaea communities are mainly differentiated at the island scale. The results highlight distinct spatial scales of organization for major microbial domains in tropical forest soils. However, the absence of environmental physicochemical measurements limits direct identification of the environmental drivers underlying these patterns.